An exploratory short‐term double‐blind randomized trial of varenicline versus nicotine patch for smoking cessation in women. (29th March 2015) - Gray, Kevin M.; McClure, Erin A.; Baker, Nathaniel L.; Hartwell, Karen J.; Carpenter, Matthew J.; Saladin, Michael E.
Abstract Aims Within a parent study examining ovarian hormone effects on smoking cessation in women, we conducted an exploratory short‐term trial of varenicline versus transdermal nicotine patch. Design Double‐blind double‐dummy randomized trial. Setting Single‐site out‐patient research clinic in the United States. Participants Female smokers, ages 18–45 years and averaging ≥10 cigarettes per day for at least 6 months (n = 140). Interventions Participants were randomized to receive a 4‐week course of (a) varenicline tablets and placebo patches (n = 67) or (b) placebo tablets and nicotine patches (n = 73). Two brief cessation counseling sessions were provided for all participants. Measurements The outcome of primary clinical interest was 2‐week end‐of‐treatment abstinence. Secondary outcomes included 1‐ and 4‐week end‐of treatment abstinence and abstinence at a post‐treatment follow‐up visit occurring 4 weeks after treatment conclusion. Breath carbon monoxide (≤ 10 parts per million) was used to confirm biochemically self‐reported abstinence. Findings Two‐week end‐of‐treatment abstinence was achieved by 37.3% (25 of 67) of varenicline participants and by 17.8% (13 of 73) of nicotine patch participants [odds ratio (OR) = 2.7, 95% confidence interval (CI) = 1.3–6.0, P = 0.011]. One‐week (44.8 versus 20.6%, OR = 3.1, 95% CI = 1.5–6.6, P = 0.003) and 4‐week (22.4 versus 9.6%, OR = 2.7, 95% CI = 1.0–7.2, P = 0.043) end‐of‐treatment abstinence similarly favored varenicline, although post‐treatment follow‐up Russell Standard abstinence was not significantly different between groups (23.9 versus 13.7%, OR = 2.0, 95% CI = 0.8–4.7, P = 0.126). Conclusion In an exploratory 4‐week head‐to‐head trial in female smokers, varenicline, compared with nicotine patch, more than doubled the odds of end‐of‐treatment abstinence, although this diminished somewhat at post‐treatment follow‐up.